2020
DOI: 10.3390/electronics9020254
|View full text |Cite
|
Sign up to set email alerts
|

Sol-Gel Processed Yttrium-Doped SnO2 Thin Film Transistors

Abstract: Y-doped SnO2 thin film transistors were successfully fabricated by means of sol-gel process. The effect of Y concentration on the structural, chemical, and electrical properties of sol-gel-processed SnO2 films was investigated via GIXRD, SPM, and XPS; the corresponding electrical transport properties of the film were also evaluated. The dopant, Y, can successfully control the free carrier concentration by suppressing the formation of oxygen vacancy inside SnO2 semiconductors due to its lower electronegativity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(10 citation statements)
references
References 27 publications
0
10
0
Order By: Relevance
“…1c consists of a strong peak at a low binding energy and a shoulder peak at a high binding energy, corresponding to the bonds of lattice oxygen (O L ) and oxygen-decient defects like oxygen vacancies and hydroxyl (O D ), respectively. 27,[36][37][38][39][40][41][42][43] For the DAP modied TiO 2 sample, O 1s shis to a lower binding energy compared to that for the control one, which further evidences the interaction between DAP and TiO 2 . 35 Besides, the component concentration of O L and O D can be reected by the area ratio of the corresponding peaks, and aer modifying the TiO 2 lm with DAP, the area ratio of O L : O D is increased from 67.4 : 32.6 to 72.9 : 27.1, strongly indicating that the hydrogen phosphate anion combines with the oxygen vacancy of the TiO 2 lm to reduce the concentration of O D along with the simultaneous formation the lattice oxygen for an increased O L concentration, 20,44 which cross-veries the above analysis results and fully demonstrates that the modication of DAP effectively passivates the oxygen vacancy defects on the TiO 2 lm surface.…”
Section: Resultsmentioning
confidence: 79%
“…1c consists of a strong peak at a low binding energy and a shoulder peak at a high binding energy, corresponding to the bonds of lattice oxygen (O L ) and oxygen-decient defects like oxygen vacancies and hydroxyl (O D ), respectively. 27,[36][37][38][39][40][41][42][43] For the DAP modied TiO 2 sample, O 1s shis to a lower binding energy compared to that for the control one, which further evidences the interaction between DAP and TiO 2 . 35 Besides, the component concentration of O L and O D can be reected by the area ratio of the corresponding peaks, and aer modifying the TiO 2 lm with DAP, the area ratio of O L : O D is increased from 67.4 : 32.6 to 72.9 : 27.1, strongly indicating that the hydrogen phosphate anion combines with the oxygen vacancy of the TiO 2 lm to reduce the concentration of O D along with the simultaneous formation the lattice oxygen for an increased O L concentration, 20,44 which cross-veries the above analysis results and fully demonstrates that the modication of DAP effectively passivates the oxygen vacancy defects on the TiO 2 lm surface.…”
Section: Resultsmentioning
confidence: 79%
“…In 2020, Zhang et al [21] prepared Ga doped SnO 2 -TFT (GTO-TFT) at 450 • C by spin coating, and found that with the Ga content rising from 20% to 60%, the V O decreased from 30.24% to 17.18%, while the I off of TFT correspondingly decreased from 10 −3 A to 10 −11 A. In addition, other commonly used dopants such as Sb, Cr, Zr, Y [22][23][24][25][26] can also reduce the V O concentration, but low reserves and a certain toxicity limit their practical application.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, incorporating Si has the potential to lower the carrier concentration of SnO 2 films and improve the device's performance. However, there are few studies of Si doping into SnO 2 by the solution method, and most of them require a high processing temperature (>450 • C) [26,31].…”
Section: Introductionmentioning
confidence: 99%
“…High-quality pure metal oxide layers can be easily formed. Their structural, optical, chemical, and electrical properties can be tuned by changing the annealing conditions or the precursor component ratio [ 24 , 25 , 26 , 27 ]. The starting precursors for the sol-gel process are in the liquid phase.…”
Section: Introductionmentioning
confidence: 99%